Voice Based Email for Blind (International Journal of Innovative Research in Computer Science & Technology, 2021)
Now-a-days internet has become one of  the basic aids for day-to-day living. Every human being is  widely accessing the knowledge, information and also  using for communication through internet. However,  blind people face difficulties in accessing these net-based  information, also in using any service provided through  internet. The advancement in computer based accessible  systems has opened up many possibilities for the visually  impaired across the worlds in a wide way. Audio based  virtual environment like, the screen readers and many  voice-based search engines have helped Blind people to  access internet applications immensely. We describe the  Voice-based mail system architecture that can be used by  a Blind person to access e-Mails easily and efficiently.  The contribution made by this research has enabled the  Blind people to send and receive voice-based e-Mail  messages with the help of a computer.
Keywords: Text-to-Speech convertor; Speech-to Text convertor; Chatbot